Death by black hole [compact disc, unabridged] : and other cosmic quandaries - Tyson, Neil deGrasse (Blackstone Audiobooks, 2007)
A collection of essays on the cosmos, written by an American Museum of Natural History astrophysicist, includes "Holy Wars," "Ends of the World," and "Hollywood Nights."